Strategi Pengembangan Bisnis Time Juice: Membawa Waktu dan Rasa ke Masa Depan - Ai Sopiah; Bhenu Artha (Jaanur Elbarik Indonesia, 2025)
This study aims to determine the development strategy through Time Juice business model planning which aims to plan the right business model in the future and its application so that it can compete with similar competitors. The research method used is interviews with juice drink business owners and data analysis from various sources. The results showed that the development strategy through Time Juice business model planning can be done by focusing on the application of the Business Model Canvas design through field studies related to competitor analysis and consumer behavior. This becomes a reference in designing Time Juice's business development strategy which focuses on the use of quality raw materials, product innovation, product variety, and the application of creative marketing strategies. The development strategy through business model planning is a reference for Time Juice businesses in increasing product value and competitiveness in the market. This research contributes to the development of food industry business strategies and can be a reference for other dim sum entrepreneurs in developing effective future business development strategies.